PENGARUH PROFITABILITAS DAN OPINI AUDIT TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Asmedi, Syamsul (Perwira Journal of Economics & Business, 2022)
This study aims to examine the effect of profitability and audit opinion on audit delay with firm size as moderating. The independent variables used are profitability and audit opinion, the dependent variable used is audit delay and the moderating variable used is company size. This type of research is classified as quantitative research. The data used is secondary data. The population in this study is the mining sector companies listed on the Indonesia Stock Exchange for the period 2014-2019 as many as 43 companies. Sampling in this study using purposive sampling technique. Based on purposive sampling obtained 174 companies. The analysis technique used is multiple regression analysis and MRA. Data processing using Eviews 10. Keywords: Profitability, Audit Opinion, Audit Delay, Company Size